Bagaimana Hasil Belajar Matematika Siswa SD berdasarkan Berat dan Tinggi Badan antara Siswa Laki-laki dan Perempuan? - Al Ayyubi, Ibnu Imam; Andriani, Anita; Noerzanah, Firda; Alhamdani, Deden Abdul Hamid; Rahmawati, Siti (Program Studi Pendidikan Guru Sekolah Dasar, 2024)
Currently, students' mathematical abilities are still relatively low and are found in several schools. This research aims to analyze students' mathematics learning outcomes based on school origin, reviewing the students' gender, weight, and height. This research used a quantitative approach which was carried out at SDN Pasirbanteng, MI Ar-Ridhwan, and MIS Pasirpogor I with survey methods and Analysis of Variance tests to see differences and interactions. The population in this study was all students at SDN Pasirbanteng, MI Ar-Ridhwan, and MIS Pasirpogor I with a sample of 41 students at SDN Pasirbanteng, 33 students at MI Ar-Ridhwan, and 20 students at MIS Pasirpogor I for a total of 94 students. This research instrument uses a test that tests the data analysis requirements used, consisting of a normality test using Kolmogorov-Smirnov and Shapiro-Wilk with the help of SPSS version 26 software. The research results show no differences and interactions between gender, height, and weight of students on mathematics learning outcomes based on the student's school origin. This is based on the Two Ways ANOVA statistical test with data that has homogeneity and normality of the data received. So, for further research, it is hoped that an analysis of students' mathematics learning outcomes can be carried out based on the student's gender, distance from domicile to school, and parents' income to see whether there are significant differences and interactions with their learning outcomes.